Roles of Type VI Secretion System in Transport of Metal Ions - Yang, Xiaobing; Liu, Hai; Zhang, Yanxiong; Shen, Xihui (Frontiers in Microbiology, 2021)
The type VI secretion system (T6SS) is a transmembrane protein nanomachine employed by many Gram-negative bacteria to directly translocate effectors into adjacent cells or the extracellular milieu, showing multiple functions in both interbacterial competition and bacteria-host interactions. Metal ions transport is a newly discovered T6SS function. This review summarizes the identified T6SS functions and highlights the features of metal ions transport mediated by T6SS. The published microorganisms and their corresponding T6SS dependent metal ions transport mode is summarized, and the regulation factors for metal ions transport byT6SS are discussed.